DIFFICULTIES IN LAPAROSCOPIC CHOLECYSTECTOMY: CONVERSION VERSUS SURGEON'S FAILURE - Ali, Aun; Saeed, Summaya; Khwaja, Rabel; Samnani, Sunil Sadruddin; Farid, Farah Naz (Journal of Ayub Medical College Abbottabad, 2016)
Background: Laparoscopic cholecystectomy is considered to be gold standard treatment for symptomatic gall stones. Despite several benefits there are still disadvantages of laparoscopic cholecystectomy in difficult cases where anatomy is disturbed even in experienced hand. Aim of this study is to identify advantages of early conversion to open cholecystectomy in difficult cases and how it should not be associated with surgeon's failure. Methods: Observational study was conducted at tertiary care hospital of Karachi, Pakistan from January 2012 till June 2015. All patients who presented to general surgery department with symptomatic gall stones and planned for laparoscopic cholecystectomy was included in the study. Demographic data was collected. Preoperative workup includes baselines investigations with liver profile test and imaging study (ultrasound scan). All patient underwent laparoscopic cholecystectomy at first. Operative difficulties, incidence of conversion, reason for conversion and complication intra-operative or postoperative were recorded. Data was analyzed using SPSS 20. Results: Out of 1026 patients, 78.26% (803) were female. Mean age of patients were 41.30±8.43 years (range 26-68 years). Common presenting symptoms were pain at upper abdomen and dyspepsia. Most of the patients had multiple gall stones (93.85%). Nine hundred and ninety-two patients (96.68%) of patients underwent successful laparoscopic cholecystectomy. This includes patients in whom dissections were difficult because of disturbed anatomy of calots triangle. Only 3.13% of patients were converted to open cholecystectomy. There was a significant difference (<0.05) in complications observed between completed and converted cholecystectomies. Conclusion: Conversion from laparoscopic to open procedure should be done in cases of technically difficult situations to avoid significant mortality and morbidity. Surgeons experience had a pivotal role in determining its need and justification. Keywords: Laparoscopic Cholecystectomy; Conversion; Gall stones; Failure; Open cholecystectomy